The Conceptualization of VIVO (Visual Interactive Virtual Object) in the Transformation of Science Learning in Elementary Schools - Gingga Prananda (Innovative: Journal Of Social Science Research, 2026)
The rapid advancement of Artificial Intelligence (AI) technology offers significant opportunities for transforming instructional media in elementary schools; however, its implementation often lacks a strong theoretical foundation. This study aims to conceptualize VIVO (Visual Interactive Virtual Object) as a novel learning framework for elementary science education to bridge students’ understanding of abstract concepts. In this study, VIVO is positioned not as a commercial representation, but as a conceptual paradigm in learning design. VIVO is defined as a learning concept based on intelligent digital media that integrates dynamic visualization, precise interactivity, and adaptive virtual objects to facilitate students’ active and contextual construction of conceptual understanding. The research employs a qualitative descriptive method using content analysis and a literature review that synthesizes theories of multimedia learning, cognitive load, and constructivism. The findings indicate that the VIVO concept consists of four main components: AI-supported dynamic visualization, guided interactivity, contextual virtual objects, and adaptive visual scaffolding. From a theoretical perspective, VIVO has the potential to reduce extraneous cognitive load and enhance students’ active engagement through interactive manipulation of virtual representations. In conclusion, this study provides a theoretical foundation for the development of intelligent digital learning media that function not merely as tools for information delivery, but as instruments for knowledge construction. These findings imply the need for a paradigm shift in instructional media design toward more interactive and adaptive learning environments. The proposed VIVO framework is expected to serve as a basis for future research and development (R&D) studies to empirically examine its effectiveness in improving students’ science learning outcomes in real classroom settings.